Did the Covid-19 Pandemic Trigger Herding Behavior? - Komalasari, Puput Tri; Qalby, Zahrin Haznina; Alhaqi, Vanessa Ryan (Universitas Prasetiya Mulya, 2024)
This study aims to examine the influence of the COVID-19 pandemic on mutual fund herding in Indonesia. The research population comprises open-end mutual funds in Indonesia. By adopting the purposive sampling method, we selected the stock mutual funds registered from 2017 to 2022 as our research sample. We define the 2017-2019 period as before COVID-19 and 2020-2022 as during COVID-19. This study employs CSAD and CSSD as proxies for return dispersion by considering two types of indices as benchmarks, namely LQ45 and IDX Composite. Our study found that COVID-19 did trigger mutual fund herding. However, we failed to find herding behavior when there is a large market movement. Instead, we found reverse herding.